Alcohol: Immunomodulatory effects and cancer - Juan C. Molina; Jesús D. Guerrero-Morán; Claudia González-Espinosa (Permanyer, 2023)
Alcohol consumption has been linked to numerous pathologic conditions, including infectious diseases and several types of cancer. Alcohol exerts its modulatory effects on the immune system (IS) in a dose- and time-dependent manner. Numerous studies indicate that these alterations affect responses such as peripheral inflammation or decreased antibody production and promote chronic inflammation, leading to cell death. The molecular mechanisms underlying these effects involve generating an oxidative tissue environment, producing cell damage-associated molecular patterns (DAMPs), and activating pattern recognition receptors. In particular, toll-like receptors and their signaling system emerge as central elements whose activity is altered by alcohol intake. There is also some epidemiological evidence demonstrating the causal role of alcohol in the development of various types of cancer, such as head-and-neck cancer, esophageal cancer, colorectal cancer, liver cancer, and breast cancer. Most recent evidence suggests that factors related to alcohol consumption and cancer include increased levels of acetaldehyde, production of reactive oxygen species, alteration in DNA methylation, and modifications in retinoid metabolism. In addition, changes associated with alcohol use on the IS and intestinal microbiota may favor the growth of some types of tumors.